Patients enrolled in randomised clinical trials are not representative of critically ill patients in clinical practice: Observational study focus on tigecycline - Zimmermann, Johannes B.; Bruckner, Thomas; Martin, Eike; Hoppe-Tichy, Torsten; Swoboda, Stefanie (International journal of antimicrobial agents, 2013)
It is being increasingly recognised by clinicians and scientists that participants in randomised clinical trials (RCTs) of antibiotics of last resort do not represent the patients who will later be treated with these drugs. Data on this subject are limited and have not been investigated systematically. This observational study aimed to examine this hypothesis quantitatively, using the example of tigecycline. To evaluate the influence of recruitment, patients eligible for clinical trials were retrospectively compared with ineligible patients regarding baseline and clinical characteristics as well as outcome parameters, e.g. length of hospital stay, intensive care unit (ICU) stay, ventilation and mortality. The clinical characteristics of 187 patients illustrated differences in the nature and severity of disease, co-morbidities and outcome. Eligible and ineligible patients differed in a number of parameters, e.g. median APACHE II score (15.5 vs. 28.0), number of liver transplantations (5% vs. 18%; P=0.048), septic shock (21% vs. 49%; P=0.001), need for mechanical ventilation (30% vs. 79%; P<0.001), mean length of ICU stay (19.3 days vs. 40.7 days) and death (19% vs. 46%; P=0.001). Critically ill patients were under-represented in clinical trials. Moreover, only a minority of patients in clinical practice (13%) were potentially eligible for a pivotal RCT. The disparities likely result from strict exclusion criteria in RCTs and recruitment bias. These data emphasise the importance of including critically ill patients in RCTs of antibiotics against multiresistant bacteria in order to account for those who will later be treated.